Ontogenetic biomechanics of tufted (Sapajus) and untufted (Cebus) capuchin mandibles - Polvadore, Taylor A.; Yoakum, Caitlin B.; Taylor, Parker M.; Holmes, Megan A.; Laird, Myra F.; Chalk-Wilayto, Janine; Kanno, Cláudia Misue [UNESP]; de Oliveira, José Américo [UNESP]; Terhune, Claire E. (Wiley, 2024)
Objectives: Cortical bone geometry is commonly used to investigate biomechanical properties of primate mandibles. However, the ontogeny of these properties is less understood. Here we investigate changes in cortical bone cross-sectional properties throughout capuchin ontogeny and compare captive versus wild, semi-provisioned groups. Tufted capuchins (Sapajus spp.) are known to consume relatively hard/tough foods, while untufted capuchins (Cebus spp.) exploit less mechanically challenging foods. Previous research indicates dietary differences are present early in development and adult Sapajus mandibles can resist higher bending/shear/torsional loads. Materials and methods: This study utilized microCT scans of 22 Cebus and 45 Sapajus from early infancy to adulthood from three sample populations: one captive Cebus, one captive Sapajus, and one semi-provisioned, free-ranging Sapajus. Mandibular cross-sectional properties were calculated at the symphysis, P3, and M1. If the tooth had not erupted, its position within the crypt was used. A series of one-way ANOVAs were performed to assess differences between and within the sample populations. Results: Mandible robusticity increases across ontogeny for all three sample populations. Sapajus were better able to withstand bending and torsional loading even early in ontogeny, but no difference in shear resistance was found. Semi-provisioned, free-ranging Sapajus tend to show increased abilities to resist bending and torsional loading but not shear loading compared to captive Sapajus. Discussion: This study helps advance our understanding of the primate masticatory system development and opens the door for further studies into adaptive plasticity in shaping the masticatory apparatus of capuchins and differences in captive versus free-ranging sample populations.
Keywords: durophagy; mastication; microCT